The promise of total automation - Faucheret, Anne 1981-; Jourdan, David 1974- (Sternberg Press, 2017)
The exhibition "The Promise of Total Automation" investigated our relationship to a world of machines, technological objects, and electronic devices. The prospect of a fully automated future—while acutely reshaping the notions of work, production, and value creation—also feeds emancipatory scenarios ultimately leading to the end of labor. Total automation is upon us but its liberating promise is yet to be claimed. This book surveys the literature on that story. It tracks its fabric, layers, and mediations, and unfolds a bibliography and chronology of automation and of its promises.